An?lise de desempenho de t?cnicas de sensoriamento espectral baseadas em autovalores em canais com desvanecimento de Nakagami-m e rice - Silva J?nior, Ricardo Augusto da (2013)
Efficient use of bandwidth is presented as a guideline project within the area of wireless communications systems. Currently, regardless of the technology within the telecommunications networks (wired or wireless, optical systems and satellites), the concern with the spectral efficiency and the intelligent use of bandwidth resources is widespread. At the same time, there is an underutilization of the spectrum that is questioned by the telecommunications sector. Research initiatives are moving towards achieving an optimum of quality, robustness and intelligence in the use of spectrum for various telecom services. In this scenario, there is the Cognitive Radios (CRs) technology, which is trying to solve the problem of under-utilization of the spectrum through the process of spectrum sensing. Thus, it is necessary that the spectral sensing techniques are efficient because the random behavior of the channel affects the signal detection process. In this work, an investigation was conducted of the performance of spectrum sensing techniques based on eigenvalues under different channel models. The probability distribution of Nakagami-m was chosen for channel modeling and a simulator has been developed to address the theoretical phase statistics of fading, and open topic discussed in the literature. With this, four spectral sensing techniques (RLRT, ED, GLRT and ERD) were verified and simulated on the Nakagami-m fading channels. The performance of the detection probability of the techniques mentioned was also observed in Rice fading channels in order to check out various propagation scenarios. Comparisons were made between the techniques in different scenarios considering multipath and the knowledge (or not) of noise variance It was verified that the RLRT is more efficient than energy detector in Nakagami-m fading channels in different regimes of signal-to-noise ratio. In the case of techniques that do not require knowledge of the noise power (GLRT and ERD), was verified superiority of the test GLRT to the technique ERD in Nakagami-m and Rice multipath fading channels.